Research of information security database vulnerabilities - Корченко, Александр Григорьевич; Казмирчук, Светлана Владимировна; Арджомандифард, Алиреза; Панивко, Татьяна Валерьевна (Ukrainian Information Security Research Journal, 2016)
Existing public database vulnerabilities store a variety of data about known vulnerabilities of information systems resources. Descriptions of vulnerabilities contain both precondition and assessment, describing the result of the realization of attacks that exploit these vulnerabilities. Often experts involved in research for the condition of information systems security, think of a choice of relevant databases. These bases, on certain criteria, can effectively be used to build a variety of assessment systems of the information security state, such as risk assessment systems. In this connection, it was examined a wide range of relevant databases and defined the criteria what enables to carry out a comparative analysis. This will provide an opportunity to enhance the effectiveness of rating the security state of information systems resources.